Peran Pola Komunikasi dalam Human Relations Mahasiswa terhadap Toxic Relationship - Tiara Rua Moulina; Hesa Agus Pratiwi; Azizatun Nafsyiah; April Laksana (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
This study aims to determine the role of communication patterns in student human relations on the emergence and dynamics of toxic relationships. Communication patterns, both verbal and nonverbal, are important elements in interactions between individuals that affect the quality of interpersonal relationships. In the context of university students, communication patterns are often influenced by the level of emotional maturity, cultural background, and social environment. Unhealthy communication patterns, such as domination, manipulation, or a tendency to avoid conflict, can be the main trigger of toxic relationships. Conversely, healthy communication with openness, empathy, and respect can prevent toxic relationships and improve problematic relationship dynamics. This research uses a type of qualitative research using the literature study method sourced from books, journals regarding the research discussed by examining the Role of Communication Patterns in Student Human Relations Against Toxic Relationship. Communication patterns have a significant role in shaping the dynamics of student relationships, including toxic relationships. Healthy communication patterns, including openness, empathy, and respect can prevent toxic relationships, while unhealthy communication patterns such as domination, manipulation, or closure, are often the main triggers. Students who lack interpersonal communication skills are vulnerable to getting trapped in toxic relationships, which can have a negative impact on their mental health and academic performance. Increased self-awareness, use of assertive communication, boundary setting, and external support are key steps to prevent or overcome toxic relationships. With positive communication patterns, students can build healthy relationships, support personal development, and create a harmonious social environment.